Using the redistribution between routing protocols to find best route - Hamad, Aqeel (University of Thi-Qar Journal of Science, 2013)
Routers can forward packets through an internetwork by maintaining routing information in a databasecalled a routing table. The routing table typically contains the address of all known networks and routinginformation about that network such as: Interface, Routing Path, Next Hop, Route Metric (Cost) and RouteTimeout Routers build and maintain their routing database by periodically sharing information with otherrouters. The exact format of these exchanges is based on the routing protocol.The output of this study is Compare between routing protocols (Routing Information Protocol v2 andEnhanced Interior Gateway Routing Protocol).Design and implementation by using (GNS3) Graphical Network Simulator and we also Configuring theexchange of routing information between routing protocols is called route redistribution. Redistribution can bedone between various Interior Gateway Routing Protocol routing protocols.